- #1

- 18

- 0

a little rough on this simplification, is this correct?

solving for "u"

E = mc^2 / (root)(1-u^2/c^2)

(root)(1-u^2/c^2) = mc^2/E

1 - u^2/c^2 = (mc^2/E)^2

1 = (mc^2/E)^2 + u^2/c^2

c^2 = (mc^2/E)^2 (c^2) + u^2 -> (sq root everything)

u = c - mc^3/E

pretty bad i don't know this basic simplification, but it'll all come back quickly enuf

thanks for the help

-Neil

solving for "u"

E = mc^2 / (root)(1-u^2/c^2)

(root)(1-u^2/c^2) = mc^2/E

1 - u^2/c^2 = (mc^2/E)^2

1 = (mc^2/E)^2 + u^2/c^2

c^2 = (mc^2/E)^2 (c^2) + u^2 -> (sq root everything)

u = c - mc^3/E

pretty bad i don't know this basic simplification, but it'll all come back quickly enuf

thanks for the help

-Neil

Last edited: